Development of A Cheerful, Healthy Gymnastics Model In Learning Rhythmic Gymnastic Activities For Early Childhood Students In The Bawang Sub-District Of Batang District (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to develop a model of Senam Sehat Ceria that can be used in learning rhythmic gymnastics activities for early childhood (PAUD) in Bawang District, Batang Regency. This research approach uses a development method (research and development), which involves needs analysis, model design, implementation, and evaluation. The results of the study indicate that the Senam Sehat Ceria model can improve children's motor skills, creativity, and enthusiasm for rhythmic gymnastics activities. This model is designed with simple and fun movements, and is in accordance with the characteristics of early childhood development. This study contributes to innovations in interactive and fun rhythmic gymnastics learning in PAUD. The results of the implementation evaluation show that this model is effective and well-received by PAUD teachers. Innovation in learning rhythmic gymnastics activities for early childhood (PAUD) in Bawang District, Batang Regency, is the Senam Sehat Ceria model. This model is intended to be a fun, interactive learning model that is in accordance with the developmental needs of early childhood. The results of the study showed that the cheerful, healthy gymnastics model can improve children's motor skills, creativity, and their desire to participate in rhythmic gymnastics activities. The movements are designed to be easy, varied, and fun so that teachers and children can easily follow them. According to the implementation evaluation, this model helps children's social and emotional development through activities that encourage interaction and cooperation. So that with this cheerful, healthy gymnastics, it is expected to increase the enthusiasm of early childhood to learn and be active at school. Innovative, relevant, and interesting rhythmic gymnastics learning for early childhood is greatly assisted by this research. It is expected that the Happy Healthy Gymnastics model can be widely applied as part of the early childhood education curriculum, especially in physical education, because the results show that it is well-received by PAUD teachers and has a big impact on children. Thus, with this Happy Healthy Gymnastics, it will help encourage early childhood to be interested in pursuing education from an early age.